CURIOSITY FROM THE PERSPECTIVE OF COGNITIVE PSYCHOLOGY AND NEUROSCIENCE: EPISTEMOLOGICAL IMPLICATIONS FOR EDUCATION AND THE LEGAL SYSTEM - Mira Yanti Lubis; Sutan Botung Hasibuan; Nurhakima Akhirani Nasution; Fithri Choirunnisa; Elgusri; Julhadi; Ahmad Sabri (Program Studi Manajemen Pendidikan Islam, 2026)
Curiosity is a fundamental aspect of human cognitive development that plays a crucial role in the formation and development of knowledge. From a cognitive psychology perspective, curiosity is understood as an internal drive that arises due to an information gap. In neuroscience, this phenomenon is related to the activity of the dopamine system, hippocampus, and prefrontal cortex, which support learning, memory, and decision-making. This study aims to analyze curiosity from a cognitive psychology and neuroscience perspective and examine its epistemological implications in education and the legal system. The method used is library research with a qualitative-descriptive approach and content analysis of relevant scientific literature. The results of the study indicate that curiosity has a strong neurobiological basis and plays a key role in the exploration and learning process. Epistemologically, curiosity is the foundation for critical and reflective knowledge construction. The implication in education is the importance of implementing inquiry-based learning, while in the legal system, curiosity needs to be managed ethically to support the search for truth and justice.